A KNOWLEDGE MANAGEMENT-BASED DECISION-MAKING MODEL FOR PLANNING PATIENT DISCHARGE IN THE NIGERIAN HEALTH CARE SYSTEM (FULafia Journal of Science and Technology, 2019)
The Nigerian health care system (NHCS) is bedraggled with myriads of problems that had caused a major landslide of setback since independence. More pathetic is the fact that Nigeria health care has no concrete discharge planning (DP) and processes for patients admitted into her hospitals. The process of discharge is a critical phase in hospital management, and correction of it is a major strategy in NHCS. This is a major issue which nobody is looking into as it affects the convalescence of the patients. Effective Discharge Planning(DP) requires practitioners to have appropriate, patient personalized and updated knowledge in order to be able to make informed and holistic decisions about a patients’ discharge. This paper examines the role that Knowledge Management (KM) plays in planning an effective discharge plan. This paper also proposes KM models in healthcare and integrates KM with DP in the form of a KM based DP model for Nigeria health care system as the use of information and communications technology will increase productivity and efficiency in healthcare and large amounts of stored data will be of help to decision makers in practice.
Keywords: Knowledge Management; Healthcare; Discharge Planning; Care; Patient